TI_GERICHTE 12.2016.155 vom 29. März 2018 , Responsabilità dell'avvocato - revoca dell'amministratore della SA - abuso di diritto - TI Tribunale d'appello (2018)
Responsabilità dell'avvocato - revoca dell'amministratore della SA - abuso di diritto